Associations between the awakening responses of salivary α-amylase and cortisol with self-report indicators of health and wellbeing among educators. (February 2016) - Katz, Deirdre A.; Greenberg, Mark T.; Jennings, Patricia A.; Klein, Laura Cousino
Abstract: Chronic job stress makes teachers susceptible to burnout and negative health outcomes. Identifying factors that contribute to burnout is critical for teachers' health and their students' learning. This cross-sectional study examined the daily cycle of stress-related biomarkers (alpha amylase and cortisol) and self-reports of stress, burnout and psychological wellbeing in 64 middle school teachers. Reports of depersonalization and ambition were associated with less steep awakening responses in cortisol whereas ambition and perceived stress were associated with a less steep alpha amylase awakening response. Findings indicate that examining multiple dimensions of burnout is useful in understanding teacher wellbeing. Highlights: Reports of depersonalization and ambition were associated with less steep awakening responses in cortisol. Ambition and perceived stress were associated with a less steep sAA awakening response. Increased emotional suppression as associated with more total cortisol output.